The effect of intraoperative inosine infusion on transplant outcomes in deceased-donor kidney transplant recipients - You Luo; Yang Zhang; Zuofu Tang; Jinhua Zhang; Ning Na; Hengjun Xiao (Renal Failure)
Objectives It is unknown when inosine was first employed as a renoprotective agent in the context of kidney transplantation procedures. However, there is no clinical evidence to support a protective role of inosine. The aim of this study was to investigate the effect of inosine on graft recovery.Patients and methods Data related to donors and recipients were retrieved from relevant records between 2015 and 2023. A total of 1138 kidney transplant cases were identified, including 1005 recipients who received a bolus of 1000 mg inosine and 133 recipients who did not receive inosine during transplantation surgery. The endpoints of the analysis included recipient recovery after transplantation as assessed by delayed graft function (DGF), peak estimated glomerular filtration rate (eGFR) after transplantation, and unfavorable graft function recovery.Results Given the high dimensionality of the donor and recipient variables, propensity score weighting analyses were conducted. No significant differences in the risk of DGF (OR = 0.80 [0.52, 1.22], p = 0.301), unfavorable graft function recovery (OR = 0.95 [0.61, 1.51], p = 0.842) or peak eGFR after transplantation (β = 1.61 [−4.33, 7.56], p = 0.594) were observed between the inosine and no-inosine groups via overlap weighting analysis.Conclusions Intraoperative infusion of 1000 mg of inosine has no effect on graft recovery after kidney transplantation. Therefore, the practice of using inosine during kidney transplantation surgery is not supported by evidence.